The sexual dimorphic inguinal glands of the frog species Ololygon centralis (Anura: Hylidae) at light and transmission electron microscopy - Brito,Pedro (2019)
ABSTRACT The anuran skin characteristically has different types of glands, most of which are microscopic and are spread throughout the skin. Some species have specialized regions where glands agglomerate, forming macroglands. The description of the external morphology of Ololygon centralis (Pombal & Bastos, 1996) revealed the presence of an inguinal gland. Ololygon centralis is the only species of the genus that has a macrogland. The present study found these inguinal macroglands to be present only on male specimens, thus characterizing it as a sexually dimorphic skin gland. Microscopic analysis revealed that these glands are composed of many syncytial units involved by myoepithelial cells. The center of the syncytium is full of a proteinaceous secretion with a basic pH and the absence of sugar residues. Similar glands observed in other anuran species have been associated with pheromone production, suggesting that the inguinal glands described for O. centralis males may have a similar function.